Thinking in time: an introduction to Henri Bergson - Guerlac, Suzanne (Cornell University Press, 2006)
Bergson and Bergsonisms -- From the certainties of mechanism to the anxieties of indeterminism -- Time and free will (Essai sur les données immédiates de la conscience) -- Matter and memory -- Channels of contemporary reception -- Current issues